Accra-Tema. Das Werden einer afrikanischen Großstadt - Karmon, Yehuda (ERDKUNDE, 1967)
This paper attempts to explain some of the reasons for the rapid growth of Accra, the capital of Ghana, from 140 000 in 1948 to 390 000 in 1960 and approximately 500 000 in 1965. Most of the locational factors - harbour facilities, inland communications, distance to settlement centres - are negative, and the main reason for its position in the hierarchy of towns in the former Gold-Coast Colony is its dryer and cooler climate, which attracted the British administration to set up its headquarters in this town. All further development was the outcome of its central ad ministrative functions, which were even strengthened after independence by the centralistic and monolithic structure of the regime of Nkrumah. The last few years have brought a further impulse to economic development with the construction of the Volta Dam at Akosombo and the deep-water harbour at Tema. In its wake Accra became, in addition to its administrative and financial functions, the centre of industrial development and the main port of the country, and therefore in the true sense a primate city. The second part of the paper deals with the internal structure of the town and the anatomy of its spatial growth. Here a parallel to the development of European towns can be seen insofar as land-uses tend to perpetuate themselves. The historical core turned into the central business district, while different functions spread out in sectors according to the model of Homer Hoyt.